2022
DOI: 10.3390/curroncol29120717
|View full text |Cite
|
Sign up to set email alerts
|

Quality of End-of-Life Care in Gastrointestinal Cancers: A 13-Year Population-Based Retrospective Analysis in Ontario, Canada

Abstract: Population-based quality indicators of either aggressive or supportive care at end of life (EOL), especially when specific to a cancer type, help to inform quality improvement efforts. This is a population-based, retrospective cohort study of gastrointestinal (GI) cancer decedents in Ontario from 1 January 2006–31 December 2018, using administrative data. Quality indices included hospitalizations, emergency department (ED) use, intensive care unit admissions, receipt of chemotherapy, physician house call, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Further, our previous work found that younger age, residency in the three lowest-income quintile neighbourhoods, and rurality were associated with increased odds of experiencing aggressive care at EOL. However, sex was not included as a predictor in this model [ 16 ]. In this secondary analysis, we found that the female population may be driving the associations between increased odds of aggressive care at EOL and younger age.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, our previous work found that younger age, residency in the three lowest-income quintile neighbourhoods, and rurality were associated with increased odds of experiencing aggressive care at EOL. However, sex was not included as a predictor in this model [ 16 ]. In this secondary analysis, we found that the female population may be driving the associations between increased odds of aggressive care at EOL and younger age.…”
Section: Discussionmentioning
confidence: 99%
“…The same relationship, however, may not appear for females, who, despite education level, may have lower incomes due to the longstanding gender wage gap in addition to traditional gender norms driving increased caregiver responsibilities and less income-generating work outside the home [42,43]. Other studies showed an association between increased risk of aggressive EOL care and lower income [16,[44][45][46], though, to our knowledge, this is the first study to directly compare how income may affect the aggressiveness of care for each sex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations